Laplace transform of saw-tooth function

1

a

2a

3a

We notice for this problem, f (t ) =

1 t and the period, p = a a

The definition of Laplace transform can now be applied: F ( s ) = ∫ e − st f (t )dt
0 a 2a a ∞

Since each piece needs to be integrated separately, (i.e. ∫ + ∫ + ... ), apply summation:
0

F (s) = ∑

∞ ( n +1) a na

n=0

e − st

t dt a

The integration can be accomplished using integration by parts, where u = t and dv = − se − st dt , resulting with: ( n +1) a 1 − st − te − ∫ e − st dt na as

[

]

=− =−

1  − st 1 − st  te + e  as  s   na

( n +1) a

1  1  ( n + 1)ae − sa ( n +1) − nae − san + e − sa ( n +1) − e − san   as  s 

(

)

Let’s take this one piece at a time. The first piece is: (n + 1)ae − sa ( n +1) − nae − san

nae − sa ( n +1) + ae − sa ( n +1) − nae − san e − sa ( n +1) = e − san − sa = e − san * e − sa nae − san * e − sa + ae − san * e − sa − nae − san ae − sa (ne − san + e − san ) − nae − san applying the summation …
n =0 ∞ ∞ ∞

(1)

(2)

∑ (2) = ae

− sa

n=0

∑ n (e

− sa n

) + (e − sa ) n − ∑ na (e − sa ) n
n=0

as n approaches infinity, the summation terms multiplied by n go to zero since the exponential term decreases much faster than the linear term increases:
− sa − sa n ) = ∑ (2) = ae ∑ (e n=0 ∞ ∞

n =0

(1 − e − sa ) , since this is a geometric series )

ae − sa

The second piece is:

1 − sa ( n +1) e − e − san s

(

From (1), this can be rearranged in the form: 1 − san − sa e − sa − a − san − san e *e −e = (e ) s s applying summation.... e − sa − a ∞ − sa n e − sa − a 1 ) = * ∑ (e s s (1 − e − sa ) n=0 Putting it all together… F (s) = − =− 1  ae − sa (e − sa − 1)  +   as  1 − e − sa s(1 − e − sa )   

(

)

(ae − sa ) − (e − sa − 1) as (1 − e − sa ) as 2 (1 − e − sa ) (ae − sa ) + (1 − e − sa ) =− as (1 − e − sa ) as 2 (1 − e − sa )
F (s) = 1 as 2 − e − sa s (1 − e − sa )

(

(

)

)